2018
DOI: 10.7181/acfs.2018.02096
|View full text |Cite
|
Sign up to set email alerts
|

New anthropometric data for preoperative planning in orbital wall fracture treatment: the use of eyelid drooping

Abstract: BackgroundThe presence of enophthalmos is an important determinant in the decision of orbital wall fracture surgery. We proposed eyelid drooping as a new anthropometric diagnostic measure and analyzed whether eyelid drooping is associated with enophthalmos.MethodsThis retrospective study was performed from January 2014 to December 2016. A total of 75 patients with blowout fractures were studied. One experimenter measured the degree of enophthalmos using a Hertel exophthalmometer at 1 week after trauma and at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this study, a direct, positive correlation was identified be-tween the enophthalmometric difference and the fracture size, and the value of 1.81 cm 2 was determined as the cutoff to predict the occurrence of enophthalmos with a sensitivity of 0.543 and a specificity of 0.724. Although this value does not significantly differ from the criterion of 2 cm 2 in adults, and considering that previous studies [6,10,13] have reported that defects sized up to 2.3-2.6 cm 2 should not cause cosmetic problems, it can be established as a sufficient criterion for the pediatric population. Given that the average age of the non-operated patients was 11.95 ± 3.04 years, and that their midface would have developed similar to that of an adult, this may have introduced bias.…”
Section: -Specificitymentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, a direct, positive correlation was identified be-tween the enophthalmometric difference and the fracture size, and the value of 1.81 cm 2 was determined as the cutoff to predict the occurrence of enophthalmos with a sensitivity of 0.543 and a specificity of 0.724. Although this value does not significantly differ from the criterion of 2 cm 2 in adults, and considering that previous studies [6,10,13] have reported that defects sized up to 2.3-2.6 cm 2 should not cause cosmetic problems, it can be established as a sufficient criterion for the pediatric population. Given that the average age of the non-operated patients was 11.95 ± 3.04 years, and that their midface would have developed similar to that of an adult, this may have introduced bias.…”
Section: -Specificitymentioning
confidence: 74%
“…In adults, indications for surgical treatment of orbital fractures are: radiographic evidence of an extensive fracture that can result in muscle incarceration, causing double vision, enophthalmos, or exophthalmos; orbital volume change; and visual acuity deficit or blow-in fracture caused by a presumed invasion of the optical canal by the fracture that does not react to steroids. The criteria for extensive pure orbital fractures are a fracture size of over 2 cm 2 or a bony defect greater than 50% [5][6][7][8][9][10].…”
Section: Surgical Indication Analysis According To Bony Defect Size Imentioning
confidence: 99%